Properties of dynamically vulcanized ethylene-propylene-diene copolymer/polypropylene blends - TAŞDEMİR, MÜNİR (WILEY, 2007)
In this study, vulcanized thermoplastic elastomers were produced through the formation of crosslinks with peroxide for different ratios of ethylene-propylenediene copolymer to polypropylene. Mixing was performed with a twin-screw extruder. Afterward, the yield, tensile strength, elastic modulus, elongation, Izod impact strength, hardness, melt flow index, Vicat softening point, heat deflection temperature, and density of the crosslinks were determined. The thermal transition temperatures and microstructure were determined with differential scanning calorimetry and scanning electron microscopy, respectively. (C) 2007 Wiley Periodicals, Inc.
Keywords: blends; elastomers; poly(propylene) (PP); thermoplastics; vulcanization; EPDM